MENCARI DASAR BERSAMA: TINJAUAN HISTORIOGRAFIS DALAM MENCARI VISI INDONESIA - Andreo Fernandez Rajagukguk (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
Indonesia is a unique country that has thousands of islands. This unique wants to signify the diversity of ethnic groups and languages in Indonesia. Jean Gelman Taylor in her book, Indonesia. Peoples and Histories (2003), believes that with the diversity of ethnic groups and languages in Indonesia, there are many stories or history of all these ethnic groups that have not even been revealed at all. Of course, this is a "loss" for national history and the identity of certain ethnic groups when talking about "becoming Indonesia"; bearing in mind "being Indonesia" is a form of power over causal relations in observable social interaction, which can provide a strong foundation for Indonesia. However, apart from these beliefs, Indonesia with a variety of ethnic groups and languages, of course, has a long journey or a long history of unifying these ethnic groups. This paper will look back (read: history) to investigate the vision that became the common ground for the formation of Indonesia, as well as a reference in laying a solid foundation for Indonesia today (after independence).  Keywords: Nasionalism, Vision, Landscape, History, hybrid, Power.